Foreign Learning Platforms in Russian Education System: Potential Capacity Evaluation and Risks Forecasting - A. A. Onosov; E. V. Bryzgalina; N. E. Savina; S. V. Tumanov (Высшее образование в России)
The article deals with an analytical description of problems caused by integration of foreign learning platforms into the Russian education system.  It provides the main results and conclusions reached within the frame of the  fundamental quantitative research project. The project goals were the  following: to study Russian experience in using learning platforms, foreign  ones in particular; to study abundance of foreign learning platforms; to  reveal and specify typical risks caused by their functioning in Russian  education sphere. The authors analyze statistical information obtained  through processing the data of survey of experts in online education. They  consider colligated opinions and assessments by professional community of  integration and application of foreign learning platforms, online courses  arrangement on them and the complex of those potential threats for Russian  education that could be caused by their use. The work notes that learning  platforms are an innovative form of education activities management, but  their integration in the national system of education is connected with a  number of risks. The article gives a contemporary review of learning  platforms in the Russian educational field in terms of their nominal  recognition, their real demand for by the experts in online education and their long-term benefits for national education. The principal criteria for  the choice of learning platforms usage in education are stated and  summarized on the basis of the empirical data. The study contains a  description of a complex of main tasks for Russian education; in the professional environment their successful solving is linked to the shift to  online education technology. Within the frame of forecasting and evaluation  of risks in education there have been defined some threats which are typical  for both domestic and foreign learning platforms as well as those which are  specific for the latter ones. Risks interpretation is based on theoretical  preliminary studies and experts’ survey data related to the subject. The  categorical range of risks obtained includes content risks, social, economic  and political risks, psychological and pedagogical risks, management risks. The authors raise the problem of regulation of foreign learning  platforms integration into the Russian education system. The work contains  the arguments for and against control in this sphere.